Haemorrhagic Colitis Caused by Dasatinib - Nishant Patodi; Nidhi Sagar; Zbigniew Rudzki; Gerald Langman; Naveen Sharma (Case Reports in Hematology)
Gastrointestinal bleeding appears to be a common adverse event associated with dasatinib therapy. Here we present a case of a 59-year-old man with chronic myeloid leukaemia (CML) developing the rarest complication of haemorrhagic colitis with dasatinib therapy which resolved rapidly after treatment withdrawal.